Burden of Heart Failure Patients in a Tertiary Level Cardiac Hospital - Kabiruzzaman, M; Malik, FN; Ahmed, N; Badiuzzaman, M; Choudhury, SR; Haque, T; Rahman, H; Ahmed, MN; Banik, D; Khan, MAM; Dutta, AK; Sayeed, S; et al. (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: Heart failure (HF) has become an increasingly frequent cause of hospital admission and carries a poor prognosis. There is a paucity of data in Indo-Asians particularly in Bangladesh on characteristics of heart failure patients. The purpose of this study was to determine the etiological factors and co-morbidity of hospitalized heart failure patients. Method: A hospital based cross sectional study was done at a tertiary cardiac hospital in Dhaka city. Hospital medical records of 14009 patients admitted between January 2005 and August 2006 were reviewed and 1970 patients with the diagnosis of HF were identified. Relevant etiological information and socio demographic data were abstracted from the hospital record files. Result: About one-seventh of total hospital admitted patient had HF. Mean age (SD) was 54.1 (15.3) years. Majority (35.79%) had ischaemic heart disease (IHD) as the principal etiological factor but this frequently coexisted with a history of hypertension (46.8%). Hypertension was considered the primary risk factor of HF in 29.14% of cases. Hypertension alone and in coexistence with other etiology was found in 48.07% (947) cases. Diabetes Mellitus (DM) co-existed with IHD in 41.4% (292) and it (32.64%) was found more prevalent in Dilated Cardiomyopathy (DCM) patient with HF. Conclusions: The mean age of hospitalized HF patients is remarkably lower than other related studies done abroad. The single most common etiology for HF is ischemic heart disease in this population. Hypertension is the most common risk factor. Measures to prevent ischaemic heart disease and control of risk factors are essential to prevent premature onset of HF. DOI: 10.3329/jbcps.v28i1.4640 J Bangladesh Coll Phys Surg 2010; 28: 24-29